A country-level analysis comparing hospital capacity and utilisation during the first COVID-19 wave across Europe. Issue 5 (May 2022) - Berger, Elke; Winkelmann, Juliane; Eckhardt, Helene; Nimptsch, Ulrike; Panteli, Dimitra; Reichebner, Christoph; Rombey, Tanja; Busse, Reinhard
Highlights: Hospital and ICU capacity varied widely, both before and during COVID-19 pandemic. The number of COVID-19 patients did not exceed the capacities of acute care beds. In many countries ICU surge capacity was necessary to accommodate demand. Hospital resource use was not consistently related with SARS-CoV-2 incidence. Hospital utilisation also depends on service delivery patterns and public health strategies. Abstract: Background: The exponential increase in SARS-CoV-2 infections during the first wave of the pandemic created an extraordinary overload and demand on hospitals, especially intensive care units (ICUs), across Europe. European countries have implemented different measures to address the surge ICU capacity, but little is known about the extent. The aim of this paper is to compare the rates of hospitalised COVID-19 patients in acute and ICU care and the levels of national surge capacity for intensive care beds across 16 European countries and Lombardy region during the first wave of the pandemic (28 February to 31 July). Methods: For this country level analysis, we used data on SARS-CoV-2 cases, current and/or cumulative hospitalised COVID-19 patients and current and/or cumulative COVID-19 patients in ICU care. To analyse whether capacities were exceeded, we also retrieved information on the numbers of hospital beds, and on (surge) capacity of ICU beds during the first wave of the COVID-19 pandemic from the COVID-19 Health System Response Monitor (HSRM). Treatment days and mean length of hospital stay were calculated to assess hospital utilisation. Results: Hospital and ICU capacity varied widely across countries. Our results show that utilisation of acute care bed capacity by patients with COVID-19 did not exceed 38.3% in any studied country. However, the Netherlands, Sweden, and Lombardy would not have been able to treat all patients with COVID-19 requiring intensive care during the first wave without an ICU surge capacity. Indicators of hospital utilisation were not consistently related to the number of SARS-CoV-2 infections. The mean number of hospital days associated with one SARS-CoV-2 case ranged from 1.3 (Norway) to 11.8 (France). Conclusion: In many countries, the increase in ICU capacity was important to accommodate the high demand for intensive care during the first COVID-19 wave.